Understanding the interaction between selected microplastics and the toxic dye "Congo red" in water - Kannan, N.; Yanushiya, J.; Shri Lasha, R.; Bandala, E.R. (Elsevier, 2025)
This study thoroughly investigated the adsorption of Congo Red (CR) dye onto various microplastics (MPs), including high-density polyethylene (HDPE), polyvinyl chloride (PVC), low-density polyethylene (LDPE), poly propylene (PP) and polyethylene terephthalate (PET). Initial adsorption capacities (qe) revealed that HDPE had the highest value (21.90 mg/g), followed by PVC (4.2 mg/g), LDPE (3.7 mg/g), PP (3.1 mg/g) and PET (2.8 mg/g). Based on these findings, HDPE and PVC were selected for detailed analysis. Adsorption experiments were conducted under controlled conditions: CR concentration of 100 mg/L, adsorbent dosage of 2 g/L, pH of 5, and temperature of 303 K. Isotherm studies indicated that HDPE followed the Freundlich model (R2 - 0.99), while PVC was best described by the Redlich-Peterson model (R2 - 0.97). Kinetic analysis showed that HDPE adhered to the Bangham model (reliable ((R2 = 0.9267, 0.950, 0.988, and 0.988) R2 values obtained for all the concentrations), highlighting pore-filling mechanisms. The conclusion, supported by FTIR analysis, indicates no significant changes in HDPE’s functional groups after the adsorption. In contrast, PVC followed a pseudo-second order kinetic model (reliable R2 values (0.999, 0.765, 0.956, 0.972) obtained for all the concentrations), suggesting chemisorption, confirmed by FTIR changes in the C–Cl bonds. The optimal pH for adsorption was 5 for HDPE and 4 for PVC. Both processes were exothermic with intraparticle and film diffusion identified as rate-limiting steps. Maximum adsorption capacities (qmax) were 110.1 mg/g for HDPE and 8.1 mg/g for PVC. Desorption experiments were conducted only for HDPE due to PVC’s lower adsorption. The highest desorption for HDPE occurred at pH 4 (5.7 mg/L) with an adsorbent dosage of 2 g/L. This study underscores the dual environmental threat posed by MPs, which not only adsorb organic pollutants like CR but also release them under certain conditions. While this research advances our understanding of MPs as pollutant carriers, future work should focus on their desorption behavior in complex, real-world environments. Further studies on other organic pollutants and microplastic types in real wastewater systems are also recommended.
Keywords: Microplastics; Interaction; Congo red dye; Adsorption; Mechanism; Water